2021
DOI: 10.5194/gmd-14-3995-2021
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Adriatic Sea and Coast (AdriSC) climate component – a COAWST V3.3-based coupled atmosphere–ocean modelling suite: atmospheric dataset

Abstract: Abstract. In this evaluation study, the coupled atmosphere–ocean Adriatic Sea and Coast (AdriSC) climate model, which was implemented to carry out 31-year evaluation and climate projection simulations in the Adriatic and northern Ionian seas, is briefly presented. The kilometre-scale AdriSC atmospheric results, derived with the Weather Research and Forecasting (WRF) 3 km model for the 1987–2017 period, are then thoroughly compared to a comprehensive publicly and freely available observational dataset. The eval… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 81 publications
0
19
0
Order By: Relevance
“…Within the AdriSC modelling suite, the climate componentbased solely on the basic moduleis dedicated to the study of long-term kilometer-scale processes occurring in the Adriatic region. The complete description of the AdriSC climate component, including the set-up of the atmospheric and oceanic models, is presented in Denamiel et al (2020aDenamiel et al ( , 2021b and Pranić et al (2021). Additionally, the performances of the AdriSC climate component have already been thoroughly assessed for both the atmosphere (Denamiel et al 2021b) and the ocean (Pranić et al 2021).…”
Section: Adrisc Climate Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the AdriSC modelling suite, the climate componentbased solely on the basic moduleis dedicated to the study of long-term kilometer-scale processes occurring in the Adriatic region. The complete description of the AdriSC climate component, including the set-up of the atmospheric and oceanic models, is presented in Denamiel et al (2020aDenamiel et al ( , 2021b and Pranić et al (2021). Additionally, the performances of the AdriSC climate component have already been thoroughly assessed for both the atmosphere (Denamiel et al 2021b) and the ocean (Pranić et al 2021).…”
Section: Adrisc Climate Modelmentioning
confidence: 99%
“…The complete description of the AdriSC climate component, including the set-up of the atmospheric and oceanic models, is presented in Denamiel et al (2020aDenamiel et al ( , 2021b and Pranić et al (2021). Additionally, the performances of the AdriSC climate component have already been thoroughly assessed for both the atmosphere (Denamiel et al 2021b) and the ocean (Pranić et al 2021). Overall, the evaluation revealed that the AdriSC climate component is better suited to study the long-term processes over the Adriatic region than the classical Regional Climate Models (RCMs) used in the Mediterranean Sea.…”
Section: Adrisc Climate Modelmentioning
confidence: 99%
“…Nevertheless, these results still outperform the ones of the previous Mediterranean RCMs evaluated in the Adriatic Sea, which exhibited biases above 3.0 for the salinity and below −3.0 • C for the temperature in the northern Adriatic (e.g. L 'Hévéder et al, 2013;Di Luca et al, 2014;Sevault et al, 2014;Parras-Berrocal et al, 2020). Additionally, indepen- dently of the subdomains, the analysis of the vertical profiles shows that the temperature and salinity biases often present a peak in the vicinity of the thermocline depth, which can probably be linked to an inaccurate representation of vertical diffusivity and vertical mixing in the AdriSC ROMS models.…”
Section: Discussionmentioning
confidence: 67%
“…Finally, the cold summer SST biases are also known to be higher in the northern Adriatic Sea, reaching below −3 • C on average (e.g. L 'Hévéder et al, 2013;Di Luca et al, 2014;Sevault et al, 2014;Parras-Berrocal et al, 2020). Consequently, it can be safely said that the results obtained with the AdriSC ROMS 3 km model are at least within the ranges of the known cold SST biases of the Mediterranean models.…”
Section: Discussionmentioning
confidence: 73%
“…The Adriatic Sea and Coast (AdriSC) modeling suite was recently implemented to simulate the atmospheric and oceanic processes driving the Adriatic basin circulation at scales ranging from long-term regional climate change to minute-by-minute impacts of extreme events along the coasts (Denamiel, Šepić, Huan, et al, 2019;Denamiel, Šepić, Ivanković & Vilibić, 2019). Due to the modular approach developed within the system, the AdriSC modeling suite can be run in both operational and research modes and has been successfully used in various applications such as climate warming research (Denamiel, Pranić, et al, 2020;Denamiel, Pranić, et al, 2021) or operational forecast within the Croatian Meteotsunami Early Warning System (CMeEWS; Denamiel, Šepić, Huan, et al, 2019;Denamiel, Šepić, Ivanković & Vilibić, 2019;Tojčić et al, 2021).…”
Section: Adrisc Modeling Suitementioning
confidence: 99%